On the Formation of Planets in the Milky Way’s Thick Disk - Tim Hallatt; Eve J. Lee (The Astrophysical Journal)
Exoplanet demographic surveys have revealed that close-in (≲1 au) small planets orbiting stars in the Milky Way’s thick disk are ∼50% less abundant than those orbiting stars in the Galactic thin disk. One key difference between the two stellar populations is the time at which they emerged: thick-disk stars are the likely product of cosmic noon (redshift z ∼ 2), an era characterized by high star formation rate, massive and dense molecular clouds, and strong supersonic turbulence. Solving for the background radiation field in these early star-forming regions, we demonstrate that protoplanetary disks at cosmic noon experienced radiation fields up to ∼7 orders of magnitude more intense than in solar neighborhood conditions. Coupling the radiation field to a one-dimensional protoplanetary disk evolution model, we find that external UV photoevaporation destroys protoplanetary disks in just ∼0.2–0.5 Myr, limiting the timescale over which planets can assemble. Disk temperatures exceed the sublimation temperatures of common volatile species for ≳Myr timescales, predicting more spatial homogeneity in gas chemical composition. Our calculations imply that the deficit in planet occurrence around thick-disk stars should be even more pronounced for giant planets, particularly those at wide orbital separations, predicting a higher rocky-to-giant planet ratio in the Galactic thick disk versus thin disk.